The Measurement of Thermal Conductivity Variation with Temperature for Sn-Based Lead-Free Binary Solders - Demir, Mustafa; Aksoz, Sezen; Ozturk, Esra; Marasli, Necmettin (SPRINGER, 2014)
The variations of thermal conductivity with temperature in the Sn-based lead-free binary solders, Sn-10 wt pct X (X = Ag, In, Bi, Cu, Sb, Zn), were measured by using the linear heat flow apparatus. The thermal conductivities of Sn-based lead-free solders at their melting temperature were obtained from graphs of thermal conductivity variation with temperature. The variations of electrical conductivity with temperature for same solders were also determined from the Wiedemann-Franz (W-F) equation by using the measured values of thermal conductivity.
Keywords: ELECTRICAL CONDUCTIVITIES; INTERFACIAL ENERGIES; PURE METALS; ALLOYS; LIQUID; SOLIDIFICATION; Materials Science; Metallurgy & Metallurgical Engineering